(a+b)²
how can we solve
Answers
Answered by
5
(a+b)² =a²+b²+2ab.
hope it's helpful to you.
hope it's helpful to you.
naseem5:
(a+b) (a+b) =a(a+b) +b(a+b) =a.a+a.b+b.a+b.b=a square +b square +2ab
Answered by
2
Expand (a+b) ^2 According to the following identity
![{(a + b)}^{2} = {a}^{2} + {b}^{2} + 2ab {(a + b)}^{2} = {a}^{2} + {b}^{2} + 2ab](https://tex.z-dn.net/?f=+%7B%28a+%2B+b%29%7D%5E%7B2%7D+%3D+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+%2B+2ab)
Now, put the values and get the result
Now, put the values and get the result
Similar questions